The influence of contextual factors on knee osteoarthritis self-management and education interventions in rural settings of the Western Cape - Coetzee, Marisa (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScPhysio)--Stellenbosch University, 2019.